Classifying Sustainable Development Goal trajectories: A country-level methodology for identifying which issues and people are getting left behind. (November 2019) - McArthur, John W.; Rasmussen, Krista
Highlights: A harmonized methodology can translate SDG targets into an empirical framework pertinent to each country's challenges. Of 169 SDG targets, 35 include quantified and measurable country-level outcomes; 43 are assessable through proxy targets. A clear SDG diagnostic framework can distinguish between policies that are succeeding and those meriting a new approach. A methodological focus on "no one left behind" suggests even Canada is only fully on track for one of the 16 SDGs assessed. The human scale of SDG shortfalls can be estimated; Canada has approximately 54, 000 lives at stake. Abstract: How useful are the Sustainable Development Goals for conducting empirical analysis at the country level? We develop a methodological framework for answering this question, with special emphasis on the SDGs' normative ambition of "no one left behind." We first classify all 169 SDG targets and find that 78 incorporate an outcome-focus that is quantitatively assessable at the country level, including 43 through a systematic approach to establishing "proxy targets." We then present a framework for diagnosing the embedded diversity of absolute and relative indicator trajectories in a harmonized manner, based on a country's share of its starting gap on course to be closed by the relevant deadline. In turn, we present a method for estimating the human consequences of falling short on targets, measured by the number of lives at stake and people's basic needs at stake. As a case study, we apply the framework to Canada, an economy not commonly examined in the context of global goals. We are able to assess a total of 61 targets through the use of 70 indicators, including 28 indicators drawn from the United Nations' official database. Overall, we find Canada is on course to succeed on 18 indicators; to cover at least half but less than the full objective on 7 indicators; to cover less than half the required distance on 33 indicators; and to remain stagnant or move backwards on 12 indicators. Among indicators assessed, the country is only fully on track to achieve one SDG. Shortfalls suggest approximately 54, 000 Canadian lives at stake and millions of people left behind on issues like poverty, education, intimate partner violence, and access to water and sanitation. Our diagnostic framework enables considerable, if only partial, quantification of a country's SDG challenges, recognizing the wide range of contexts for underlying data availability and societal problems.